2017
DOI: 10.4236/mi.2017.61001
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Open-Source Plant-Canopy Monitoring System

Abstract: Many agricultural applications, including improved crop production, precision agriculture, and phenotyping, rely on detailed field and crop information to detect and react to spatial variabilities. Mobile farm vehicles, such as tractors and sprayers, have the potential to operate as mobile sensing platforms, enabling the collection of large amounts of data while working. Open-source hardware and software components were integrated to develop a mobile plant-canopy sensing and monitoring system. The microcontrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The P-B and P-C have calibrations that are closest in values to the sensor manufacturer's specifications, and thus have an advantage for liquid volume measurement. Similar studies have shown the use of ultrasonic sensors to be well fitted and accurate for the liquid level in similar type of containers, though with much larger diameters relative to the sensors' cone pattern [4]. The operational performance data show how well the calibration, described previously, can be applied to new data for each tube and pipe, as seen in Figure 4.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The P-B and P-C have calibrations that are closest in values to the sensor manufacturer's specifications, and thus have an advantage for liquid volume measurement. Similar studies have shown the use of ultrasonic sensors to be well fitted and accurate for the liquid level in similar type of containers, though with much larger diameters relative to the sensors' cone pattern [4]. The operational performance data show how well the calibration, described previously, can be applied to new data for each tube and pipe, as seen in Figure 4.…”
Section: Resultssupporting
confidence: 59%
“…The autonomous measurement of liquid volume has multiple applications in the fields of precision agriculture and precision livestock farming, both in operations and development of new technologies. Such technologies could include water intake monitoring in livestock, sprayer nozzle analysis, and chemical tank level monitoring [1][2][3][4]. Of particular interest is the liquid volume measurement for sprayer nozzle patternator tables.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor described by [5] was used in this study. It consisted of a batterypowered, microcontroller-based system containing a Bluetooth radio, global positioning receiver, four infrared temperature sensors (plant canopy temperature measurements), four ultrasonic distance sensors (plant height measurement), micro secure digital card, and voltage regulation components.…”
Section: Data Collectionmentioning
confidence: 99%
“…Recently, [5] developed a plant-canopy monitoring system with inexpensive sensors and open-source software, demonstrated how the system components worked, and discussed data output and potential applications of the data as a survey tool. The sensor system can be easily mounted on an agricultural vehicle such as a tractor to record plant height, plant canopy temperature, and location data as the device is moved throughout the field.…”
Section: Introductionmentioning
confidence: 99%
“…Open hardware platforms are easy to realize and use; their low cost, coupled with the increasing amount of information sharing, supports the rapid development of new-generation, inexpensive, and very flexible scientific instrumentations [ 19 , 20 ]. Ultrasound-based high-throughput sensors or platforms have been proposed for use in different crops [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ], mostly in the on-the-go mode.…”
Section: Introductionmentioning
confidence: 99%